(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The aim of the present study was to examine the effects of unilateral plyometric training on elastic strength and explosive power among athletes. To achieve the purpose of the study twenty-four male athletes (jumpers & sprinters) were randomly selected as subjects from Anna Stadium, Palayamkottai. Tirunelveli, Tamilnadu, India and their age were ranged from 18 to 25 years. The athletes were assigned at random into two groups of each twelve players (N=12). Group-I underwent unilateral plyometric training and Group–II acted as control group who did not attended any special training other than their daily college schedule curriculum. The duration of the training period was restricted to eight weeks for three alternative days per week. The pre and post data were collected before and immediately after the training period. The selected variables such as elastic strength and explosive power were measured by bunny hops and standing long jump test. The collected data from the two groups prior to and after the experimental treatment on selected elastic strength and explosive power were statistically analyzed by using the statistical technique of dependent-‘t’ test and analysis of covariance (ANCOVA). In all the cases 0.05 level of confidence was fixed as a level of confidence. The result of the study indicated that experimental training group (unilateral plyometric training) had shown significantly improved on elastic strength and explosive power among athletes. However, the control group had not shown any significant improvement on any of the selected variables such as elastic strength and explosive power.